2015
DOI: 10.1007/s11139-015-9704-x
|View full text |Cite
|
Sign up to set email alerts
|

Restricted k-color partitions

Abstract: Abstract. We generalize overpartitions to (k, j)-colored partitions: k-colored partitions in which each part size may have at most j colors. We find numerous congruences and other symmetries. We use a wide array of tools to prove our theorems: generating function dissections, modular forms, bijections, and other combinatorial maps. We find connections to divisor sums, the Han/Nekrasov-Okounkov hook length formula and a possible approach to a finitization, and other topics, suggesting that a rich mine of result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 22 publications
(26 reference statements)
1
14
0
Order By: Relevance
“…, where the subscripts denote the colors of the part, and by convention we write each partition in non-increasing order of its parts, and assign the colors also in nonincreasing order. This is consistent with the notation of colored ordinary partitions used by Keith [12]. Counting the partitions in this example, we see that C Λ 2 (4) = 13.…”
Section: Colored B-ary Partition Functionssupporting
confidence: 86%
See 1 more Smart Citation
“…, where the subscripts denote the colors of the part, and by convention we write each partition in non-increasing order of its parts, and assign the colors also in nonincreasing order. This is consistent with the notation of colored ordinary partitions used by Keith [12]. Counting the partitions in this example, we see that C Λ 2 (4) = 13.…”
Section: Colored B-ary Partition Functionssupporting
confidence: 86%
“…More recently, Rødseth and Sellers [16] introduced and studied b-ary overpartitions, in analogy to ordinary overpartitions that had been introduced a little earlier by Corteel and Lovejoy [4]. Ordinary overpartitions were extended to restricted multicolor partitions by Keith [12], and colored b-ary partitions have recently been studied by Ulas and Żmija [18].…”
Section: Introductionmentioning
confidence: 99%
“…When α ∈ Z + , p α (n) counts the number of partitions of n in which each term is labeled with one of α different colors, where the order of the colors does not matter [11]. Moreover, in such cases, the function η −α (τ ) = q − α 24 P (q) α (1.5)…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%
“…This easily stated function has been studied by Major P. A. MacMahon [7], George Andrews [1], and more recently Tani and Bouroubi [10], the latter specifically interested in ν 2 . The author in a recent paper [5] stated several theorems concerning ν 2 and ventured further conjectures regarding ν 2 and ν 3 , which it is the purpose of this paper to prove and expand. Despite attention from these authors, results of the kind found in other areas of partition theory, such as congruences in arithmetic progressions, have not been forthcoming; here we provide several, with a proof strategy easily adaptable to future possible candidates.…”
Section: Introductionmentioning
confidence: 84%